2022
DOI: 10.1038/s41392-022-00995-z
|View full text |Cite
|
Sign up to set email alerts
|

LDL receptor-related protein 1 (LRP1), a novel target for opening the blood-labyrinth barrier (BLB)

Abstract: Inner ear disorders are a cluster of diseases that cause hearing loss in more than 1.5 billion people worldwide. However, the presence of the blood-labyrinth barrier (BLB) on the surface of the inner ear capillaries greatly hinders the effectiveness of systemic drugs for prevention and intervention due to the low permeability, which restricts the entry of most drug compounds from the bloodstream into the inner ear tissue. Here, we report the finding of a novel receptor, low-density lipoprotein receptor-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…More importantly, low-density lipoprotein receptor-related protein 1 (LRP1) was found to localize in the blood-labyrinth barrier and inner hair cells according to new research ( Shi et al, 2022 ). As an important receptor for LTF ( Li and Guo, 2021 ), LRP1 has the potential to break the restriction of BLB and deliver LTF to the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, low-density lipoprotein receptor-related protein 1 (LRP1) was found to localize in the blood-labyrinth barrier and inner hair cells according to new research ( Shi et al, 2022 ). As an important receptor for LTF ( Li and Guo, 2021 ), LRP1 has the potential to break the restriction of BLB and deliver LTF to the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that apoVs enriched in cochlea especially stria vascularis, spiral ganglion cells and hair cells after systematic administration. Besides their smaller diameter, the mechanism behind may relate to a new-found target for blood-labyrinth barrier, LRP1 (low-density lipoprotein receptor-related protein 1) [ 52 ], which was also identified in apoVs according to our proteomics analysis (Additional file 1 : Table S1). What’s more, apoVs showed more advantages in inner ear delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Although the idea of utilizing the innate biological transport mechanisms to cross the BLB for drug delivery is still in its infancy, it could be facilitated in the near future. One recent study found that the low-density lipoprotein receptor-related protein 1 (LRP-1) on the BLB can be a potential target for shuttling therapeutics across this barrier 127 , and its therapeutic value in facilitating the NIHL treatment has not been testified yet. Another approach to be explored in this field is cell-mediated drug delivery.…”
Section: Translational Dilemma From Animals To Humanmentioning
confidence: 99%